Cross-Cultural Differences in a Global "Survey of World Views". (January 2015) - Saucier, Gerard; Kenner, Judith; Iurino, Kathryn; Bou Malham, Philippe; Chen, Zhuo; Thalmayer, Amber Gayle; Kemmelmeier, Markus; Tov, William; Boutti, Rachid; Metaferia, Henok; Çankaya, Banu; Mastor, Khairul Anwar; et al.
We know that there are cross-cultural differences in psychological variables, such as individualism/collectivism. But it has not been clear which of these variables show relatively the greatest differences. The Survey of World Views project operated from the premise that such issues are best addressed in a diverse sampling of countries representing a majority of the world's population, with a very large range of item-content. Data were collected online from 8, 883 individuals (almost entirely college students based on local publicizing efforts) in 33 countries that constitute more than two third of the world's population, using items drawn from measures of nearly 50 variables. This report focuses on the broadest patterns evident in item data. The largest differences were not in those contents most frequently emphasized in cross-cultural psychology (e.g., values, social axioms, cultural tightness), but instead in contents involving religion, regularity-norm behaviors, family roles and living arrangements, and ethnonationalism. Content not often studied cross-culturally (e.g., materialism, Machiavellianism, isms dimensions, moral foundations) demonstrated moderate-magnitude differences. Further studies are needed to refine such conclusions, but indications are that cross-cultural psychology may benefit from casting a wider net in terms of the psychological variables of focus.